LAND EVALUATION BY PHYSIOGRAPHIC ANALYSIS IN THE SAVANNA BELT OF WESTERN NIGERIA - FAGBEMI, AYODELE; FAYEMI , A. A. A.; AGBOOLA, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A study of land evaluation in connection with agricultural development was carried out in the Iganna area, North West of Oyo, Nigeria. By mapping the area into physiographic units which are fully characterized, a very simple categorization of the land units into capability classes was made. Factors considered in the grouping include soil topographic and climatic factors and land use pattern. Most of these factors were fully described or indexed in the course of the survey while the data on the rest were collected from literature. It was found that physiographic analysis adequately mapped the area into units of similar soil characteristics. The factors which are considered very important to land use in the area are also very similar within the mapping units. Thus, a capability grouping based on this basic information is found to have a high degree of credibility. Under the prevailing  economic conditions and the urgency for a speedy development of agricultural potential in developing countries, there seems to be no cheaper, more rapid and yet much more reliable method of evaluating agricultural potentials than this methods.